The Field of Public Administration: From Woodrow Wilson to the Corona Pandemic - Aljarallah, Mohammed Khaled (Journal of Economic, Administrative and Legal Sciences, 2021)
This article deals with the field of public administration Starting with the efforts of Woodrow Wilson in establishing the science of public administration and its independence from politics, and the resulting development of managerial thought in the formation of the classical school and the launch of the concept of the pursuit of efficiency, then the failure of this school to include the human aspect and the subsequent orientation of researchers’ attention to include the behavioral foundation. Then calling for a review of the inevitability of the separation between administration and politics and the resulting emergence of the political approach and the development of administrative thought after that towards the direction of achieving social justice in the Minnow-Brook conferences, and what resulted from these interactions from the emergence of the new public administration and the new executive public administration and the emergence of governance in the field of public administration. Then we deal with examples of the most important global crises that affected the field of administration, such as the crisis of the events of September 11, 2001 AD, the global financial crisis in 2008 AD, and how the field interacted with its data and the effects that resulted from it. And ending with the current Corona crisis, and discussing the most important aspects of its impact in the field, and what distinguished the field of public administration after passing through these experiences and beyond.